Intracystic Papillary Carcinoma of the Breast: Report of Three Cases and Literature Review. (14th February 2012) - Ait Benkaddour, Yassir; El Hasnaoui, Sawsane; Fichtali, Karima; Fakhir, Bouchra; Jalal, Hicham; Kouchani, Mouna; Aboulfalah, Abderrahim; Abbassi, Hassan
Abstract : Intracystic papillary carcinoma is a rare malignant tumor of the breast. It occurs communally in postmenopausal women. Clinically it can be asymptomatic or manifested by a breast mass or a nipple discharge. On imaging intracystic papillary carcinoma has usually benign features. Pathologic diagnosis can be difficult at classical histological examination and identification of myoepithelial cells layer by immunohistochemical study can be useful. In the majority of cases of pure intracystic papillary carcinoma, conservative management is possible. Adjuvant therapy is still controversial and prognosis is excellent. We report three cases of intracystic papillary carcinoma diagnosed on immunohistochemical examination and managed with conservative surgery.